Prosedur Penerimaan Kas Atas Jasa Pemasangan Order Pasang Baru Untuk Pelanggan Bisnis Pada PT. TELKOM Samarinda - Yunandha Ixora Nur Utami (2021)
Procedure is an arrangement of activities that involve one or more subjects as actors in order to achieve something. An example of a procedure is the cash receipts procedure. The procedure for receiving cash can be through cash sales or receivables. One example of PT. Telkom Indonesia uses a cash receipts system based on accounts receivable. PT. Telkom Indonesia is one of the largest companies and has many subsidiaries. PT. Telkom Indonesia is also a State-Owned Enterprise (BUMN) with the number of shares held by the state. Being an advanced company requires a lot of proper systems and procedures to use. In order to minimize errors or the occurrence of cases in the environment. An error cannot be erased but can be erased, PT. Telkom Indonesia relies on several systems in it. one of the payment systems by customers of PT. Telkom Indonesia will be carried out when the service has been received and the incoming money still has to be checked again whether the owner of the order transaction is in accordance with the payment transaction made. This is done so that no money goes into the account of PT. Telkom Indonesia but don't have the right transaction.